The g-extra diagnosability of the generalized exchanged hypercube. Issue 2 (2nd April 2020) - Cheng, Eddie; Qiu, Ke; Shen, Zhizhang
Abstract : Diagnosability of a self-diagnosable interconnection structure specifies the maximum number of faulty vertices such a structure can identify by itself. A variety of diagnosability models have been suggested. It turns out that a diagnosability property of a network structure is closely associated with its relevant connectivity property. Based on this observation, a general diagnosability derivation process has been suggested. The g -extra connectivity of a graph G characterizes the size of a minimum vertex set F such that, when it is removed, every component in the disconnected survival graph, G − F, contains at least g + 1 vertices. In this paper, we discuss the aforementioned general derivation process, derive the g -extra connectivity, and then apply the aforementioned general process to reveal the g -extra diagnosability of the generalized exchanged hypercube.